Application of detailed nursing management in nosocomial infection control in the operating room (手术室细节护理管理在医院感染控制中的应用) - XU Yuanle (许远乐); WANG Xiaojie (王小洁); ZHANG Li (张莉); CHEN Ya (陈亚); QIAN Jing (钱静); XU Chaojie (徐超杰) (Association of Integrative Nursing, 2022)
Objective To evaluate the detailed nursing management in nosocomial infection control in the operation room. Methods Totally 70 patients undergoing surgical treatment were divided into the observation group (n=35) and control group (n=35) according to the admission sequence number. Patients in both control and observation received routing nursing management during the hospitalization period, and those in the observation group were given detailed nursing management. The rates of nosocomial infection and postoperative complications among patients were observed. The patient statifacion was evaluated by using a self-made questionnaire. The outcomes of theoretical knowledge and practice skills assessment among nurses were analyzed. Results There were three cases of nosocomial infection reported in the control group. The incidence of postoperative complications in the observation group was lower than that in the control group(P＜0. 05). The score of patient satisfaction assessment in the observation group was higher than that in the control group (P＜0. 01). The scores of theoretical knowledge and practice skills assessment among nurses in the observation group were higher than those in the control group(P＜0. 01). Conclusion The detailed nursing management is an effective tool for reducing risk of nosocomial infection and postoperative complications. The detailed nursing management represents a good opportunity for nurses to grow their knowledge and nursing skills, therefore improving the quality of specialized care. (目的 探讨手术室细节护理管理在医院感染控制中的应用效果。方法 选取行外科手术治疗的70例患者为研究对象, 根据入院顺序分为观察组和对照组, 各35例。对照组实施常规护理, 观察组在对照组基础上实施细节护理管理。统计两组院内感染和术后并发生情况, 采用自制量表评估患者满意度, 根据考核结果评价护理人员理论知识与实践操作水平。结果 对照组发生3例院内感染, 观察组无院内感染。观察组术后并发症发生率低于对照组, 差异有统计学意义(P＜0. 05)。观察组患者护理满意度评分高于对照组, 差异有统计学意义(P＜0. 01)。考核评价结果显示, 观察组护理人员理论知识与实践操作评分较对照组护理人员提高, 差异有统计学意义(P＜0. 01)。结论 落实细节护理管理能有效降低手术患者院内感染和并发症发生风险, 提升患者满意度。同时, 落实护理管理对提升手术室护士技能和专科护理质量具有积极意义。)